A STUDY ON THE ROLE OF RESPONSIBLE MANAGEMENT IN HIGHER EDUCATION - Bansal, Prof. Divya; G, Prof.Manjunath. (IJRDO - Journal of Applied Management Science, 2015)
The financial crisis and extensive corporate scandals during the past decade have brought about a critical debate regarding the role of business schools. Serious questions have been raised about whether and how management education can contribute to the culture of excessive greed informing this crisis. Critics claim that the disproportionate emphasis on profit maximization and shareholder value has led to neglect of the broader contexts in which businesses operate, as well as of the importance of social and environmental value creation. The objective of the current paper is to find out the role played by business and faculty members of higher education in responsible management. It is based on the case study of Copenhagen Business School where it analyses strategic implementation. This paper presents a theoretical review of how institutions of higher education are involved in the development of current and future managers.